2001
DOI: 10.1142/s0217732301005126
|View full text |Cite
|
Sign up to set email alerts
|

On the Possibility of an Astronomical Detection of Chromaticity Effects in Microlensing by Wormhole-Like Objects

Abstract: We study the colour changes induced by blending in a wormhole-like microlensing scenario with extended sources. The results are compared with those obtained for limb darkening. We assess the possibility of an actual detection of the colour curve using the difference image analysis method. *

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The gravitational lensing of a number of wormhole solutions has been studied; see, e.g., Refs. [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Observational bounds on the possible abundance of these structures are reported in Refs.…”
Section: Gravitational Lensingmentioning
confidence: 99%
“…The gravitational lensing of a number of wormhole solutions has been studied; see, e.g., Refs. [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Observational bounds on the possible abundance of these structures are reported in Refs.…”
Section: Gravitational Lensingmentioning
confidence: 99%
“…Cramer et al [23] suggested that a wormhole mouth embedded in high mass density may cause gravitational lensing effect and the resulting light enhancement can be observed. Torres et al, examined the scenario of extragalactic microlensing for natural wormholes in [102] and [103].…”
Section: Conversion Of a Wormhole Into Time Machine Was Proposed By Mmentioning
confidence: 99%
“…Interestingly, the wormhole may not only be limited to the domain of the theorist. Some very interesting studies have been performed regarding possible astrophysical signatures of such objects [15] - [19].…”
Section: Introductionmentioning
confidence: 99%